2009
DOI: 10.1017/s0140525x09991075
|View full text |Cite
|
Sign up to set email alerts
|

A socio-relational framework of sex differences in the expression of emotion

Abstract: Despite a staggering body of research demonstrating sex differences in expressed emotion, very few theoretical models (evolutionary or non-evolutionary) offer a critical examination of the adaptive nature of such differences. From the perspective of a socio-relational framework, emotive behaviors evolved to promote the attraction and aversion of different types of relationships by advertising the two most parsimonious properties of reciprocity potential, or perceived attractiveness as a prospective social part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
221
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(244 citation statements)
references
References 341 publications
(344 reference statements)
14
221
2
2
Order By: Relevance
“…Since it is claimed that women are the most powerful consumers (Tomlinson, 2007), we take this as a basis to measure Chinese women's response towards ACE-based advertisements. Since some studies suggest that women express emotions three times, on average, more than the men do (Vigil, 2009), the results presented in this study may provide some guidelines to Chinese marketing and advertising professionals to effectively boost business volumes in China by influencing Chinese women's consumption and contagion behavior. ACE research dimensions encapsulated in this study may provoke constructive discussions on advertising and marketing in the Chinese context.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Since it is claimed that women are the most powerful consumers (Tomlinson, 2007), we take this as a basis to measure Chinese women's response towards ACE-based advertisements. Since some studies suggest that women express emotions three times, on average, more than the men do (Vigil, 2009), the results presented in this study may provide some guidelines to Chinese marketing and advertising professionals to effectively boost business volumes in China by influencing Chinese women's consumption and contagion behavior. ACE research dimensions encapsulated in this study may provoke constructive discussions on advertising and marketing in the Chinese context.…”
Section: Introductionmentioning
confidence: 78%
“…Vigil (2009) notes that women may have a strong response in understanding the emotions of others, and may express their emotions more than men do. Further, women's emotionally expressive behavior may influence the consumption behavior of other people around them, for example, friends, family members, and children (Khan and Nasr, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, no study reported responses to air ion therapy by gender. Specific tests for differential responses, however, would have been of interest given that gender specific-differences are reported in the literature for many emotional parameters [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Similarity-attraction theory predicts preferences for gender-matching. This may be especially the case for females [ 6], [ 32] who have been found to prefer interacting with other females [ 37], not necessarily because they like females more than males, but because males, as a dominant group, pose more threat [ 38]. As a result of women's greater inter-dependence (relative to male independence), they tend to use similarity as the basis for social bonds [ 34].…”
Section: Virtual Assistant Characteristicsmentioning
confidence: 99%